Assessing the impact of virtual reality on the restoration of motor function in the acute period of ischemic stroke - A. S. Lakhov; M. Yu. Starikovskiy; I. E. Poverennova; M. V. Kurov; N. P. Persteneva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2024)
Aim: to evaluate the effectiveness of using virtual reality to restore motor function in patients in the acute period of ischemic stroke.Material and methods. We studied 207 patients in the acute period of ischemic stroke, who were divided into two groups by randomization: study group – 105 patients, comparison group – 102 patients. All patients received all necessary standardized therapy. Patients in the study group additionally received classes using the ReviVR device. Efficacy was assessed using the NIHSS, FMA-LE, and BBS scales.Results. On all scales studied, patients in the study group demonstrated better results in relation to the comparison group, both in terms of the final result and in terms of the level of change in indicators during the rehabilitation process. The use of virtual reality made it possible to reduce disability on the NIHSS scale to 7.0 (4.0; 9.0) points, which is better than the results of the comparison group – 9.0 (5.0; 13.0) points with a high level of significance p < 0.001. The increase in motor function according to FMA-LE in the study group was higher and amounted to 21.0 (15.0; 24.0) points versus 18.0 (7.0; 22.0) points in the comparison group with a significance level of p = 0.002. The study group also showed better results on the BBS scale – 26.0 (17.0; 34.0) versus 18.0 (5.0; 29.0) points with a significance level of p < 0.001.Conclusion. The use of virtual reality together with standardized therapy in the acute period of ischemic stroke is effective in restoring motor function of the affected lower limb, improving balance and reducing general disability in general.